Carol [videorecording (DVD)] - Blanchett, Cate, 1969-; Mara, Rooney; Paulson, Sarah, 1974-; Chandler, Kyle; Morgan, Claire, 1921-1995 (Anchor Bay Entertainment : The Weinstein Company Home Entertainment, 2016)
Two women from very different backgrounds find themselves in an unexpected love affair in 1950s New York. As conventional norms of the time challenge their undeniable attraction, an honest story emerges to reveal the resilience of the heart in the face of change. A young woman in her twenties, Therese is a clerk working in a Manhattan department store and dreaming of a more fulfilling life when she meets Carol, an alluring woman trapped in a loveless, convenient marriage.